Respuesta :

Distribute first
14-6x-2= 24+6x

Combine like terms
12-6x=24+6x

Add 6x to both sides
12=24+12x

Subtract 24 from both sides
-12=12x

Divide both sides by 12
-1=x

Final answer: x=-1
First 14-2 gives you 12
Second 12•3x gives you 36x
Third 12•1 gives you 12
Fourth 36x + 12
Fifth 6•4 =24 + 6x
Sixth 36x +12=24+6x
Seventh 36x -6x cause you subtract and move 6x to other side =30x
24-12=12 move 12 by subtract so you can put on other side
Eighth x = 2.5 then just plug in the 2.5 where you see x and if you did it right they should be equivalent